A retrospective analysis of the effects of femoral shortening osteotomy on clinical and radiologic outcomes in open reduction and Pemberton pericapsular osteotomy for Tonnis type 4 dysplasia of the hip: Femoral shortening in open reduction and Pemberton - Köse, Mehmet; Topal , Murat; Yılar , Sinan; Engin , Muhammet Çağatay; Yıldırım , Ömer Selim; Zeynel , Alperen (Journal of Surgery and Medicine, 2023)
Background/Aim: Open reduction (OR) and Pemberton’s periacetabular osteotomy (PPO) are efficient and reliable methods for treating late-diagnosed developmental dysplasia of the hip. However, various studies have reported an avascular necrosis (AVN) rate of up to 80% with this technique, which is increased in Tönnis type 4 hips. In this study, we hypothesized that femoral shortening osteotomy (FSO) would reduce the rates of AVN by decreasing the post-reduction pressure on the femoral head. Methods: In this retrospective cohort study, we reviewed patients who had undergone OR and PPO between 2006 and 2016. Only hips with Tönnis type 4 dislocation were included. The subjects were divided into two groups: Group 1, who had undergone OR+PPO, and Group 2, who had undergone OR+PPO+FSO. The Kalamchi-MacEwen system was used for AVN classification. The groups were compared regarding the pre- and postoperative acetabular indices and the rate of AVN and other complications. Results: We included 76 hips of 50 patients who met the inclusion criteria in the study. Group 1 consisted of 46 hips of 32 patients, and Group 2 consisted of 30 hips of 18 patients. The mean age of the patients was 31.5 months, and Group 1 (30 months) had a significantly lower mean age than Group 2 (34 months) (P=0.019). There were no statistically significant differences regarding the pre- and postoperative acetabular indices. In Group 1, 27 (58%) out of 46 hips had AVN, whereas the rate of AVN was ten (30%) out of 30 hips in Group 2. Out of the 27 hips with AVN in Group 1, 12 were type 1, five were type 2, and ten were type 3. Out of the 10 hips with AVN in Group 2, seven were type 1, two were type 2, and one was type 4. There was a statistically significant difference between the groups regarding the rates of AVN, with Group 2 having better outcomes not only in comparison to the rate of all AVNs (P=0.031) but also in comparison to high-grade AVNs (P=0.042) (Grade 3 and Grade 4). Conclusion: Performing FSO with OR and PPO provides a significant decrease in the rate of AVN without altering acetabular development after surgery.